2023
DOI: 10.1002/adma.202306288
|View full text |Cite
|
Sign up to set email alerts
|

Stability Issues in Electrochemical CO2Reduction: Recent Advances in Fundamental Understanding and Design Strategies

Abstract: Electrochemical CO2 reduction reaction (CO2RR) offers a promising approach to close the anthropogenic carbon cycle and store intermittent renewable energy in fuels or chemicals. On the path to commercializing this technology, achieving the long‐term operation stability is a central requirement but still confronts challenges. This motivates us to organize the present review to systematically discuss the stability issue of CO2RR. We start from the fundamental understanding on the destabilization mechanisms of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 194 publications
0
33
0
Order By: Relevance
“…Since it does not involve phase transition, the physical adsorption separation technology based on advanced porous materials can greatly reduce the energy consumption compared with traditional separation technology, coupled with the advantages of fast adsorption and desorption kinetics, low equipment cost and simple operation, which has attracted widespread attention from scientists around the world. Our recent focus is centered on complex separation systems under the actual working conditions of related industrial processes, including structure-oriented design of microporous coordination polymers, [1] analysis of adsorption and separation mechanism, [2] and synergistic sorbent separation technology of porous materials. [3]…”
Section: Favorite Chemistrymentioning
confidence: 99%
“…Since it does not involve phase transition, the physical adsorption separation technology based on advanced porous materials can greatly reduce the energy consumption compared with traditional separation technology, coupled with the advantages of fast adsorption and desorption kinetics, low equipment cost and simple operation, which has attracted widespread attention from scientists around the world. Our recent focus is centered on complex separation systems under the actual working conditions of related industrial processes, including structure-oriented design of microporous coordination polymers, [1] analysis of adsorption and separation mechanism, [2] and synergistic sorbent separation technology of porous materials. [3]…”
Section: Favorite Chemistrymentioning
confidence: 99%
“…17 environment will thermodynamically accelerate the catalyst reduction and destroy the active sites during CO 2 RR. 21,22 High proton concentration and the lack of buffer HCO 3…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, Gu and Huang et al reported that adding high concentration of alkali cations effectively inhibited HER and improved current density of CO 2 RR by enhancing the local pH or electric field. , Scientists also introduced organic additive layers on the surface of catalysts and facilitated the local alkaline environment by electrostatic confinement or cation enrichment. In addition, the interaction between key CO 2 intermediates (e.g., COOH*, OCOH*, OCCO*) and catalyst surface could be modulated by the active site engineering, thus improving the selectivity of acidic CO 2 RR. Nevertheless, the stability of CO 2 RR in acidic electrolytes is still far worse than that in alkaline, especially in acid with low concentration alkali cations . For most metal oxide catalysts, the acidic environment will thermodynamically accelerate the catalyst reduction and destroy the active sites during CO 2 RR. , High proton concentration and the lack of buffer HCO 3 – /CO 3 2– pair in acidic electrolyte are also harmful to the stability of CO 2 RR. , The catalyst degradation in acidic CO 2 RR is uncontrollable, and the evolution of local microenvironment in acid is also unclear. Therefore, understanding the mechanism of catalyst degradation and developing strategies to maintain its activity are crucial for the stability of acidic CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, in 2022, some of the most relevant researchers on the topic reported a roadmap in which they analyzed and discussed some relevant and recent advances in different aspects, including progress not only on the fundamental understanding of the reaction and the development and properties of new electrocatalysts but also on the issues and challenges related to the engineering and scaling-up of the process that can remarkably contribute toward the future commercialization of the CO 2 RR technology . During this last year, the increasing interest in this process has continued and, as proof of this, numerous and relevant reviews and articles dealing with the CO 2 RR have been published. In addition, due to their interesting and practical applications, the electrochemical reduction of CO 2 to formic acid/formate has been extensively studied. , It is also widely accepted that for future practical and industrial implementation of the CO 2 RR technology, the use of electrochemical reactors working in continuous operation mode is more convenient. ,, Besides, the employment of continuous flow conditions for electrochemical reactions has shown to provide relevant benefits over batch conditions, including not only better Faradaic efficiencies (FEs), higher selectivities, lower electrolyte loadings, and reduced energy consumption (EC) but also an improved control of the process and less difficulties for a subsequent scale-up . Particularly for CO 2 electroreduction, working in continuous operation mode also significantly contributes to minimize the limitations attributed to mass transport, which allows reaching higher CO 2 conversion rates .…”
Section: Introductionmentioning
confidence: 99%